2019
DOI: 10.1002/mame.201900442
|View full text |Cite
|
Sign up to set email alerts
|

High Thermal Conductivity Nanocomposites Based on Conductive Polyaniline Nanowire Arrays on Boron Nitride

Abstract: With the development of soft electronics, conductive composites are garnering an increasing amount of attention. The electrical conductivity, thermal conductivity, and electrical stability of conductive composites are all very important. In particular, the thermal conductivity of conductive composites is critical to the stability of their conductive properties. However, little is reported on thermal management in conductive systems. Herein, sufficiently hydroxylated boron nitride nanosheets (BN‐OH)@polyaniline… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 38 publications
(43 reference statements)
0
11
0
Order By: Relevance
“…Boron nitride (BN) platelets, which exhibit a planar structure alike graphene/ graphite, have been widely adopted as thermal conductive fillers due to their intrinsically high thermal conductivity, [25][26][27][28] outstanding electrical insulation and thermal stability as well as low dielectric properties. [29][30][31] However, the planar BN platelets tend to align along the flow direction when BN-containing polymer composites are molded using injection molding which is typical of predominant shearing effects along the flow direction, [32] thereby resulting in a great disparity between the in-plane and throughplane thermal conductivity of subsequent moldings. [33] For example, Sun et al reported that the in-plane thermal conductivity of polycarbonate (PC)/BN composites reached as high as 3.09 W mK −1 when the BN platelets are fully aligned along the flow direction whereas the thermal conductivity of randomly dispersed BN-containing counterparts was only 0.96 W mK −1 at 18.5 vol% BN.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Boron nitride (BN) platelets, which exhibit a planar structure alike graphene/ graphite, have been widely adopted as thermal conductive fillers due to their intrinsically high thermal conductivity, [25][26][27][28] outstanding electrical insulation and thermal stability as well as low dielectric properties. [29][30][31] However, the planar BN platelets tend to align along the flow direction when BN-containing polymer composites are molded using injection molding which is typical of predominant shearing effects along the flow direction, [32] thereby resulting in a great disparity between the in-plane and throughplane thermal conductivity of subsequent moldings. [33] For example, Sun et al reported that the in-plane thermal conductivity of polycarbonate (PC)/BN composites reached as high as 3.09 W mK −1 when the BN platelets are fully aligned along the flow direction whereas the thermal conductivity of randomly dispersed BN-containing counterparts was only 0.96 W mK −1 at 18.5 vol% BN.…”
Section: Introductionmentioning
confidence: 99%
“…Boron nitride (BN) platelets, which exhibit a planar structure alike graphene/graphite, have been widely adopted as thermal conductive fillers due to their intrinsically high thermal conductivity, [ 25–28 ] outstanding electrical insulation and thermal stability as well as low dielectric properties. [ 29–31 ] However, the planar BN platelets tend to align along the flow direction when BN‐containing polymer composites are molded using injection molding which is typical of predominant shearing effects along the flow direction, [ 32 ] thereby resulting in a great disparity between the in‐plane and through‐plane thermal conductivity of subsequent moldings. [ 33 ] For example, Sun et al.…”
Section: Introductionmentioning
confidence: 99%
“…[4,5] The addition of thermal conductive fillers is considered as a feasible and DOI: 10.1002/mame.202100632 effective method to enhance the overall thermal conductivity of targeted polymer matrices. [6] A variety of fillers, including metallic fillers (e.g., copper, [7] silver, [8] and nickel [9] ), carbonaceous fillers (e.g., graphene, [10] graphite, [11] and carbon nanotubes [12] ), and ceramic fillers (e.g., boron nitride, [13] silicon carbide, [14] aluminum nitride [15] ) have been employed to improve the thermal conductivity of both thermoplastics and thermosets.…”
Section: Introductionmentioning
confidence: 99%
“…Polymer-based composites are highly demanded for applications in emerging fields such as in artificial intelligence (AI) technologies, fifth-generation (5G) mobile networks, and portable electronic devices owing to their prominent advantages of remarkable thermal conductivity (TC), outstanding thermal stability, easy processability, etc. , With faster running speed and higher power density of electronic components, the thermal accumulation would be sharply increased during operation, resulting in higher heat dissipation requirements for polymer-based composites. , Therefore, exploration of polymer-based composites with high-efficiency thermal dissipation is of great significance to ensure the working reliability of next-generation modern devices.…”
Section: Introductionmentioning
confidence: 99%